Thalidomide induced Thyrotoxicosis - a Rare Case Report - Khan, Mohafizul Hoque; Nahar, Nurun (Bangladesh Journal of Nuclear Medicine, 2016)
Abstract not available Bangladesh J. Nuclear Med. 17(2): 159-160, July 2014